Identification of Morphometry and Carcass Composition of Local Sheep at Different Growth Rate - M Yamin; S Rahayu; . Komariah; M Iswahyudi; R Rachman (Faculty of Animal Science, Bogor Agricultural University, 2012)
Sheep fattening farms have been recently growing rapidly to produce better quality of sheep meat and fullfill consumer's demand. Sheep fattening and breeding farms should be developed proportionally to obtain sustainable sheep flock in the market. Twelve male lambs (less than one year old) were selected based on their average daily gain (ADG), consisting into two groups: 6 fast growing (FG) and 6 slow growing (SG) sheep. Some morphometric parameters in body and head parts of sheep and their carcass production and composition were measured and compared between the groups. The results show that chest circumference, body height, body length, head length and muzzle, top and bottom neck circumferences of FG sheep were significantly higher than in SG sheep (P0.05). It is concluded that selection of fast growing sheep can be recommended by using some morphometric parameters. The selection would not also negatively affect the weight and percentage of carcass composition.